The Impact of Job Satisfaction on Employee Performance and the Mediating Effects of Islamic Work Ethic, Islamic Organizational Culture, and Islamic Leadership - Dianingrum, Melia; Satriawan, Tegar Nur; Mugiarti, Mugiarti (Majalah Ilmiah Bijak, 2024)
The aim of this research is to examine how Islamic work ethics, leadership, and organizational culture affect employee performance mediated by job satisfaction. The study employs quantitative methods and surveys 103 employees from three Islamic banks in Purwokerto. The participants were chosen through purposive sampling, and primary data was gathered via online questionnaires. The data analysis method employed is SEM-PLS. The study findings show the acceptance of all hypotheses. Islamic work ethics, along with Islamic organizational culture and leadership, demonstrate a substantial influence on job satisfaction. Additionally, the influence of Islamic work ethics, organizational culture, and leadership on employee performance is channeled through job satisfaction as a mediating factor. This research includes job satisfaction variables as mediators, which implies that organizations can enhance employee performance through effective human resource management.